Effect of Arginine Combined with Chitosan on Quality of Postmortem Yak Meat during Maturing - Yiwen MEI; Jie LI; Rongsheng DU; Linlin WANG; Huiqin LU; Fei QIN; Pingwei LENG (Shipin gongye ke-ji, 2023)
In order to clarify the synergistic effect of different concentrations of arginine and different concentrations of chitosan on the quality of yak meat during postmortem aging and its potential mechanism, in this study, different concentrations of arginine and different concentrations of chitosan were injected into yak meat to determine their effects on the quality of yak meat during postmortem aging. The results showed that the combination of 0.4%~0.8% arginine and 1.0% chitosan could significantly increase the pH value, reduce the L*, b* values, metmyoglobin and cooking loss of yak meat during postmortem aging, and increase a* value and oxymyoglobin (P<0.05). Meanwhile, the myofibril fragmentation index, hardness, chewiness and adhesiveness of the compound treatment group were significantly higher than those of the control group during postmortem aging, while the viscosity and elasticity were significantly lower than those of the control group (P<0.05). The compound treatment increased the peroxide value and thiobarbituric acid reactive substances of yak meat. At the same time, the combination of 0.8% arginine and 1.0% chitosan significantly reduced the carbonyl content before maturation 5 day (P<0.05), but the compound treatment had no significant effect on the thiol content (P>0.05). Histological observation showed that the compound treatment was more conducive to the integrity and fullness of muscle cells, and reduced the water channel. In summary, the combination of different concentrations of arginine and different concentrations of chitosan improved the quality of postmortem yak meat during aging to a certain extent, improved its meat color stability and reduced cooking loss, promoted tenderization, and made muscle cells more complete and fuller, but it promoted fat oxidation and protein oxidation as a whole. The specific reasons and related mechanisms need to be further explored.